EFEKTIVITAS PROGRAM INTERNSHIP TERHADAP PENGEMBANGAN KOMPETENSI OPERATIONAL TELLER DAN ETIKA KERJA PADA CREDIT UNION MURA KOPA KANTOR CABANG SUNGAI DANGIN - Franciskus Darmanto; Dedy Dedy (Jurnal Pengabdian Bukit Pengharapan, 2026)
An internship program is a learning approach that holistically integrates theoretical knowledge from lectures with practical experience in a real-world work environment. This study aims to analyze the effectiveness of the internship program on the development of teller operational competencies and the formation of work ethics at the Mura Kopa Credit Union (CU) Sungai Dangin Branch Office. The operational competencies studied focus on the daily technical abilities of tellers such as savings administration, fund withdrawals, interest calculations, and credit file handling. Meanwhile, the work ethics aspect emphasizes discipline, integrity, and service professionalism. The research method used is a qualitative descriptive method with data collection techniques through participatory observation, interviews, and analysis of daily activity documentation. This study shows that the integration of theory and practice through this program has proven effective in increasing the work readiness of participants. Direct involvement in the CU Mura Kopa work ecosystem not only accelerates the mastery of technical Micro banking skills but also successfully internalizes strong work ethics values. This study concludes that synchronization between the academic world and the world of work through internships has a significant impact on improving the quality of ready-to-use human resources.